Determinants of kinesin motor polarity. - Endow, S.A.; Waligora, K.W. (Science, 1998)
The kinesin motor protein family members move along microtubules with characteristic polarity. Chimeric motors containing the stalk and neck of the minus-end-directed motor, Ncd, fused to the motor domain of plus-end-directed kinesin were analyzed. The Ncd stalk and neck reversed kinesin motor polarity, but mutation of the Ncd neck reverted the chimeric motor to plus-end movement. Thus, residues or regions contributing to motor polarity must be present in both the Ncd neck and the kinesin motor core. The neck-motor junction was critical for Ncd minus-end movement; attachment of the neck to the stalk may also play a role.